Pemanfaatan Ramuan Tradisional Lancau Wolio Terhadap Intensitas Nyeri Haid (Dysmenorrhea) Primer Pada Remaja Putri - Ernawati, Sri; Anita, Anita; Justin, Wa Ode Sitti (Jurnal Ners, 2024)
One of the most common problems experienced by young women is menstrual pain, Lancau Wolio is one of the traditional ingredients of the Wolio tribe on Buton Island, Baubau City, Southeast Sulawesi, which is believed to reduce menstrual pain. This study aims to determine the effect of the traditional Lancau Wolio on the intensity of menstrual pain in adolescent girls. This type of research is Quasi Experimental with apre-post test only design with a control group design. The sample in this study were students of class XI SMAN 2 Baubau who experienced menstrual pain as many as 30 people into 2 groups, students who consumed Lancau Wolio (intervention group and control group (not consuming Lancau Wolio). The intervention was carried out for 6 days. Data analysis using the Wilcoxon signed test.The results showed there was a difference between menstrual pain before and after treatment in the group given Lancau Wolio with a p value of 0.011 <0.05. And in the control group (without Lancau Wolio) the test results obtained a p value 0.046<0.05 which means there is a difference between menstrual pain before and after treatment in the control group. Conclusion: there is an effect of giving Lancau Wolio on reducing the intensity of menstrual pain there are young women